PENINGKATAN PEMAHAMAN HUKUM MASYARAKAT MENGENAI PERLINDUNGAN PEREMPUAN DAN ANAK KORBAN KEKERASAN DI DESA LEBO JAYA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Herman Herman; Safril Sofwan Sanib; La Sensu; Sitti Aisah Abdullah; Rahman Hasima (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
This service activity aims to increase community understanding, especially women and children, related to the protection of women and children victims of violence and efforts to overcome violence against women and children. The method used in the implementation of this service activity is to conduct socialization or counseling to the community by socializing laws and regulations regarding the protection of women and children victims of violence so as to prevent acts of violence against women and children and participate directly in the implementation of community service activities by involving all parties, which are carried out by Thematic real work lecture students Halu Oleo University so that there is synergy to complement all programs implemented by the local government and can provide strengthening in an effort to prevent acts of violence against women and children. Results of Integrated Community Service Activities Thematic Real Work Lectures held in Lebo Jaya Village, Konda District, South Konawe Regency related to the protection of women and children victims of violence, including: a) Socialization of the Sexual Violence Criminal Law, Child Protection Law and Narcotics Law which was carried out in five schools, namely Junior High School 30 South Konawe, Madrasah tsanawiyah Sirajul Munir Konsel, First middle schools 12 Konawe South, Madrasah aliyah 1 Konawe Selatan and middle schools 8 Konawe South, b) socialization of the Law on the Elimination of Domestic Violence and the Law on Child Protection, c) , c) socialization of the Sexual Violence Law and Narcotics Law, d) socialization of the impact of violence against women and children on health and the role of health services in handling cases of violence against women and children, and e) socialization of efforts to overcome violence against women and children and prevention of drug abuse. This activity can increase public understanding of the protection of women and children victims of violence which is characterized by enthusiasm and community participation in every activity carried out during the Thematic Real Work Lecture activity and can apply it in daily life related to the prevention of violence against women and children.